2020
DOI: 10.31557/apjcp.2020.21.5.1197
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-12B rs3212227 and IL-6 rs1800795 Polymorphisms with Susceptibility to Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Cervical cancer is the second most commonly diagnosed malignancy and third leading cause of cancer-related mortality among women in less developed countries (Karimi Zarchi et al., 2010; Mousavi et al., 2008). According to GLOBOCAN, cervical cancer accounts for 528,000 new cases and 266,000 deaths worldwide in 2012 (Parkin et al., 2005). Although, it has been widely accepted for several decades that Human papillomavirus (HPV) is the main risk factor for development of cervical cancer (Behtash et al., 2009; Farb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“… 18 This finding is further strengthened by multiple meta‐analysis reports which demonstrated a positive association between the G > C mutation of rs1800795 with cervical cancer. 14 , 25 , 42 , 43 Moreover, a recent meta‐analysis by Harun‐Or‐Roshid et al found that the presence of C allele increases the risk of cervical cancer in women of Asian and African ancestry. 15 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 18 This finding is further strengthened by multiple meta‐analysis reports which demonstrated a positive association between the G > C mutation of rs1800795 with cervical cancer. 14 , 25 , 42 , 43 Moreover, a recent meta‐analysis by Harun‐Or‐Roshid et al found that the presence of C allele increases the risk of cervical cancer in women of Asian and African ancestry. 15 …”
Section: Discussionmentioning
confidence: 99%
“…In a different meta‐analysis, the C allele of rs1800795 polymorphism was similarly linked to an increased risk of cervical cancer in women of Han Chinese, Brazilian, Indian, and Caucasian ethnicities 14 . However, negative association of this polymorphism with cervical cancer has also been reported in Caucasian and Brazilian women 25,28 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations